2020
DOI: 10.7150/jca.35537
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1α Promotes the Metastasis of Esophageal Squamous Cell Carcinoma by Targeting SP1

Abstract: Background: In microenvironment of malignant tumors, Hypoxia-Inducible Factors (HIF), most importantly HIF-1α, play an important role in regulation of adaptive biological response to hypoxia, promoting angiogenesis and metastasis. However, the underlying mechanism that HIF-1α regulates metastasis needs to be further clarified. Methods: The expressions of HIF-1α and SP1 were detected in 182 samples of esophageal squamous cell carcinoma (ESCC) and adjacent normal tissues by immunohistochemistry (IHC), and the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…These factors activate signal transduction pathways that lead to cell proliferation by binding to their cognate receptors ( Semenza, 2003 ). Furthermore, previous studies suggested that HIF-1α was associated with tumor metastasis, promoting cell migration and invasion ( Liu et al, 2016 ; Hu et al, 2020 ). Our immunofluorescence results revealed that the expression level of HIF-1α increased in CESCs after treatment with exosomes, indicating that HIF-1α played important roles in CESC transdifferentiation.…”
Section: Discussionmentioning
confidence: 98%
“…These factors activate signal transduction pathways that lead to cell proliferation by binding to their cognate receptors ( Semenza, 2003 ). Furthermore, previous studies suggested that HIF-1α was associated with tumor metastasis, promoting cell migration and invasion ( Liu et al, 2016 ; Hu et al, 2020 ). Our immunofluorescence results revealed that the expression level of HIF-1α increased in CESCs after treatment with exosomes, indicating that HIF-1α played important roles in CESC transdifferentiation.…”
Section: Discussionmentioning
confidence: 98%
“…Hypoxic environments can be readily found in solid malignant tumors and can lead to alterations in the expression of a number of molecular biomarkers, including HIF, carbonic anhydrase, glucose-transporter-1 and vascular endothelial growth factor ( 49 ). HIF-1α, which is activated under hypoxic conditions, is involved in the regulation of tumor cell propagation, migration, glucose metabolism and angiogenesis ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…It allows cells to adapt to hypoxic environments, contributing to invasion and metastasis. It was previously found that HIF-1α can promote the malignant progression of esophageal squamous cell carcinoma by regulating the expression specificity protein 1 ( 49 ). In the present study, it was found that both HIF-1α and PGK1 expression were upregulated due to hypoxia, suggesting an association between these two proteins.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it can bind to the SP1 promoter and regulate its transcription program in order to enhance the ability of ESCC cells to migrate and invade and promote tumor recurrence and metastasis. 55 Other studies have mentioned that it also could bind to the hypoxic response element, which located at the upstream of the Insulin-like growth factor binding protein 3 (IGFBP3) transcription initiation site, and then induce continuous translation of IGFBP3 mRNA 44 and promote ESCC cell growth and proliferation through the insulin-like growth factor-independent pathway. 56 Finally, it can also directly bind to the promoter-specific hypoxic response element of ECM metalloproteinase inducer (EMMPRIN), and further promote EC cell migration and epithelial-mesenchymal transition (EMT).…”
Section: Hypoxia Acidosis and Nutrient Depletion Are The Basic Charmentioning
confidence: 99%